A Randomized, Phase III Trial to Evaluate Rucaparib Monotherapy as Maintenance Treatment in Patients With Newly Diagnosed Ovarian Cancer (ATHENA-MONO/GOG-3020/ENGOT-ov45) - Monk, Bradley J; Parkinson, Christine; Lim, Myong Cheol; O'Malley, David M; Oaknin, Ana; Wilson, Michelle K; Coleman, Robert L; Lorusso, Domenica; Bessette, Paul; Ghamande, Sharad; Christopoulou, Athina; Provencher, Diane; et al. (Journal of clinical oncology, 2022)
ATHENA (ClinicalTrials.gov identifier: NCT03522246) was designed to evaluate rucaparib first-line maintenance treatment in a broad patient population, including those without or (BRCA) mutations or other evidence of homologous recombination deficiency (HRD), or high-risk clinical characteristics such as residual disease. We report the results from the ATHENA-MONO comparison of rucaparib versus placebo. Patients with stage III-IV high-grade ovarian cancer undergoing surgical cytoreduction (R0/complete resection permitted) and responding to first-line platinum-doublet chemotherapy were randomly assigned 4:1 to oral rucaparib 600 mg twice a day or placebo. Stratification factors were HRD test status, residual disease after chemotherapy, and timing of surgery. The primary end point of investigator-assessed progression-free survival was assessed in a step-down procedure, first in the HRD population (BRCA-mutant or BRCA wild-type/loss of heterozygosity high tumor), and then in the intent-to-treat population. As of March 23, 2022 (data cutoff), 427 and 111 patients were randomly assigned to rucaparib or placebo, respectively (HRD population: 185 49). Median progression-free survival (95% CI) was 28.7 months (23.0 to not reached) with rucaparib versus 11.3 months (9.1 to 22.1) with placebo in the HRD population (log-rank = .0004; hazard ratio [HR], 0.47; 95% CI, 0.31 to 0.72); 20.2 months (15.2 to 24.7) versus 9.2 months (8.3 to 12.2) in the intent-to-treat population (log-rank < .0001; HR, 0.52; 95% CI, 0.40 to 0.68); and 12.1 months (11.1 to 17.7) versus 9.1 months (4.0 to 12.2) in the HRD-negative population (HR, 0.65; 95% CI, 0.45 to 0.95). The most common grade ≥ 3 treatment-emergent adverse events were anemia (rucaparib, 28.7% placebo, 0%) and neutropenia (14.6% 0.9%). Rucaparib monotherapy is effective as first-line maintenance, conferring significant benefit versus placebo in patients with advanced ovarian cancer with and without HRD.